Manajemen Majelis Taklim Ulul Albab Universitas Islam Negeri Sumatera Utara - Dalimunthe, Amsal Qori; Sinulingga, Neng Nurcahyati; Diansyah, Dimas Fitra; Harahap, Agung Wahyuda; Marwan, Marwan; Daud, Muhamad Faza Fadillah; Harahap, Raju Panawan; Siregar, Habib Fansuri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This journal discusses the role of the Ulul Albab Taklim Council at the State Islamic University of North Sumatra (UINSU) as a means of fostering religious knowledge and spiritual guidance for students. Through a routine study program held three times a week, this assembly discusses various religious topics such as fiqh, akhlaq, Sufism, and tafsir, which aims to increase the spiritual intelligence of participants. In addition, collaboration with various campus organizations such as IMM, HMI, and KAHMI is a strategy to expand the reach of da'wah and increase organizational productivity. The implementation of good management functions, including planning, organizing, implementing, and controlling (POAC), is expected to achieve effective da'wah goals and be well received by the audience. This study uses a qualitative case study method, with data collection through in-depth interviews and participatory observations, to understand the dynamics of the management of the taklim council and the challenges faced. The results of the study show that the Ulul Albab Taklim Council has great potential in shaping students' character and religious understanding, as well as making a positive contribution to the academic environment at UINSU.